Hubungan antara Total Leukosit dan Trombosit pada Pasien Demam Typhoid - Priskila, Erleena; Silangit, Thomas; Rimbun, Surjadi (Jurnal Kedokteran Methodist, 2021)
Background : Infectious is a major public health problem in the world and especially in Indonesia. The presence of endotoxin in polysaccharides S.typhi bacteria stimulates the production of cytokines and causes systemic symptoms such as fever, vomiting, headache, anorexia, diarrhea, constipation. Endotoxin induces changes in bone marrow cells and causes a significant decrease in percentage of erythrocytes, leukocytes, and platelets. Method: What is done is a literature review system, where some of the existing secondary data will be analyzed and then analyzed using a system or technique in the form of documentation. The data used in this research amounted to about 15 journals, with different contents, using both languages, both English and Indonesian. Result: After conducting a search, there are 15 scientific journals that are the focus of this literature study. Conclusion : There is a significant relationship between the number of leukocytes and patients with typhoid fever, but there is no significant relationship between the value of platelets and patients with typhoid fever.